Acetyl-L-Carnitine prevents methamphetamine-induced structural damage on endothelial cells via ILK-related MMP-9 activity - Summavielle, Teresa (2014)
Methamphetamine (METH) is a potent psychostimulant highly used worldwide. Recent studies evidenced the involvement of METH in the breakdown of the blood-brain-barrier (BBB) integrity leading to compromised function. The involvement of the matrix metalloproteinases (MMPs) in the degradation of the neurovascular matrix components and tight junctions (TJs) is one of the most recent findings in METH-induced toxicity. As BBB dysfunction is a pathological feature of many neurological conditions, unveiling new protective agents in this field is of major relevance. Acetyl- L-carnitine (ALC) has been described to protect the BBB function in different paradigms, but the mechanisms underlying its action remain mostly unknown. Here, the immortalized bEnd.3 cell line was used to evaluate the neuroprotective features of ALC in METH-induced damage. Cells were exposed to ranging concentrations of METH, and the protective effect of ALC 1 mM was assessed 24 h after treatment. F-actin rearrangement, TJ expression and distribution, and MMPs activity were evaluated. Integrin-linked kinase (ILK) knockdown cells were used to assess role of ALC in ILK mediated METH-triggered MMPs’ activity. Our results show that METH led to disruption of the actin filaments concomitant with claudin-5 translocation to the cytoplasm. These events were mediated by MMP-9 activation in association with ILK overexpression. Pretreatment with ALC prevented METH-induced activation of MMP-9, preserving claudin-5 location and the structural arrangement of the actin filaments. The present results support the potential of ALC in preserving BBB integrity, highlighting ILK as a new target for the ALC therapeutic use.